The Importance of Learning Motivation in the Perspective of Islamic Education Philosophy - Samuji, Samuji (STAI MA'ARIF MAGETAN, INDONESIA, 2023)
Learning motivation is a student's encouragement or interest in learning so that student learning outcomes are achieved in accordance with educational goals. Perspective comes from Latin, namely Prespicere, which means image, seeing and view. So, in terms of terminology, perspective is a point of view for understanding or interpreting a problem. Meanwhile, in the Big Indonesian Dictionary (KBBI), perspective is a human point of view in choosing opinions and beliefs about something. Apart from that, perspective can also be said to be a balance of something. Islamic Education Philosophy is a concept of thinking about education that is based on the teachings of the Islamic religion, about the nature of human abilities so that they can be nurtured, developed and guided to become Muslim humans whose entire personality is imbued with Islamic teachings.